Axial behavior of concrete-filled double-skin tubular stub columns incorporating PVC pipes - Javed, M.F. (MDPI, 2021)
This experimental study presents concrete-filled double-skin tubular columns and demon-strates their expected advantages. These columns consist of an outer steel tube, an inner steel tube, and concrete sandwiched between two tubes. The influence of the outer-to-inner tube dimension ratio, outer tube to thickness ratio, and type of inner tube material (steel, PVC pipe) on the ultimate axial capacity of concrete-filled double-skin tubular columns is studied. It is found that the yield strength of the inner tube does not significantly affect the ultimate axial capacity of concrete-filled double-skin tubular composites. With the replacement of the inner tube of steel with a PVC pipe, on average, less than 10 strength is reduced, irrespective of size and dimensions of the steel tube. Hence, the cost of a project can be reduced by replacing inner steel tubes with a PVC pipes. Finally, the experimental results are compared with the existing design methods presented in AISC 360-16 (2016), GB51367 (2019), and EC4 (2004). It is found from the comparison that GB51367 (2019) gives better results, followed by AISC (2016) and EC4 (2004). Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.